PERAN GURU AL-QUR’AN HADITS DALAM MENINGKATKAN MINAT MEMBACA AL-QUR’AN PESERTA DIDIK DI MADRASAH IBTIDAIYAH ATTAUFIQ - MARALLENG KABUPATEN BARRU: The Role Of Al-Qur'an Hadith Teachers In Increasing Students' Interest In Reading The Al-Qur'an At Madrasah Ibtidaiyah Attaufiq - Maralleng, Barru Regency - Saputra, Imran; Darmawati (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
This study aims to obtain accurate data on the role of Qur’an and Hadith teachers in increasing students’ interest in reading the Qur’an at Madrasah Ibtidaiyah Attaufiq Maralleng Barru. The research conducted is descriptive qualitative. Data collection techniques include field observation, interviews with relevant parties, and documentation. The collected data were then displayed, reduced, verified, and presented in the form of descriptions and critical analysis. The results of the study show that the role of Qur’an and Hadith teachers as motivators is crucial in enhancing students’ interest in reading the Qur’an, particularly through the implementation of teaching strategies and methods in the Qur’an-Hadith subject. One such strategy is reading aloud, accompanied by memorization of short surahs, in addition to the use of classical methods (classical read-listen), individual methods, drill (practice) methods, and assignment methods adjusted to the material being studied